Occurrence, biology and behavior of Liogenys fuscus Blanchard (Insecta, Coleoptera, Scarabaeidae) in Aquidauana, Mato Grosso do Sul, Brazil - Rodrigues,Sérgio Roberto (2008)
Due to the importance of some Pleurosticti Scarabaeidae as agricultural pests allied to information absence on the species that occur in Brazilian Central-West region, on studies occurrence, biology and behavior on this group of scarabs were conducted. Biology and behavioral studies started with Liogenys fuscus Blanchard, 1850 (Melolonthinae), a very common species and were developed in Aquidauana, Mato Grosso do Sul. Adult beetles were collected from light traps from February 2005 to January 2007, at the experimental farm of the Universidade Estadual de Mato Grosso do Sul in Aquidauana (UEMS). In the laboratory adults were placed in plastic containers with soil with sprouts of Brachiaria decumbens Stapf (Poaceae). Eggs were transferred to a climatized chamber at 26 ± 1º C with a 12hourlight, 12hour darkness photoperiod cycle. Adult flight activity occurred in August and in September to December from 06:00 pm to 06:00 am, with the largest number of individuals flying from 07:00 to 10:00 pm. Eggs measured 1 x 1.5 mm and were laid individually or in groups in soil chambers; eggs were initially white and became yellow near hatching. The embryonic period lasted 14.3 days; first, second and third instars lasted 28.5, 48.8, and 68.2 days, respectively. The prepupal period lasted 120.2 days and the prepupa stayed inactive in soil. The mean duration of pupal stage was 27.5 days and the mean longevity of adults was 23.6 days. In laboratory the calling behavior between males and females was observed; copulation lasted, in mean, 25 minutes.